1993
DOI: 10.1101/gad.7.12a.2418
|View full text |Cite
|
Sign up to set email alerts
|

The hLEF/TCF-1 alpha HMG protein contains a context-dependent transcriptional activation domain that induces the TCR alpha enhancer in T cells.

Abstract: hLEF/TCF-Iot is a lymphoid cell-specific HMG protein that activates the distal enhancer of the gene encoding the a-subunit of the T-cell receptor (TCRot). We have shown previously that transcriptional activation by hLEF is highly dependent on the context of its binding site within the TCRa enhancer. Here, we demonstrate that hLEF contains a potent transcriptional activation domain that is separate from the HMG motif and is preferentially active in T cells. We find that hLEF/GAL4 fusion proteins can activate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
160
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(167 citation statements)
references
References 46 publications
7
160
0
Order By: Relevance
“…This region coincides with a stretch of basic amino acids located C-terminal to the HMG box proper, which has been shown to contribute to the affinity of binding in several studies (4,40,41), and more recently has been found to increase the bending angle of a DNA motif complexed to the Lef-1 HMG box (10). Our deletion and footprinting data on the Ste11 HMG box indicate that the C-terminal basic region mediates recognition of the A 11 A 12 3' flank sequence.…”
Section: Discussionmentioning
confidence: 99%
“…This region coincides with a stretch of basic amino acids located C-terminal to the HMG box proper, which has been shown to contribute to the affinity of binding in several studies (4,40,41), and more recently has been found to increase the bending angle of a DNA motif complexed to the Lef-1 HMG box (10). Our deletion and footprinting data on the Ste11 HMG box indicate that the C-terminal basic region mediates recognition of the A 11 A 12 3' flank sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins were transferred onto a polyvinyldifluoride (PVDF) membrane (Amersham, Buckinghamshire, UK) using a blotting system (NOVEX). The membrane was then incubated with antibodies against b-catenin (monoclonal, 1 : 1000), GSK3b, (monoclonal, 1 : 500) (Transduction Laboratories, Nottingham, UK), a-catenin (monoclonal, 1 : 1000; Alexis, Lausen, Switzerland) APC-COOH terminus or APC-NH 2 -terminus (polyclonal, 1 : 500; Santa Cruz Biotechnology, Santa Cruz, CA, USA), Tcf-Lef (polyclonal) and Lef-1 (monoclonal, 1 : 500; Kamiya Biomedical Company, Seattle, WA, USA) or Lef-1 antiserum (1 : 10000) (Carlsson et al, 1993). Prestained standards (SeeBlue; NOVEX) were used as weight markers.…”
Section: Immunoblottingmentioning
confidence: 99%
“…However, a more minimal reporter construct in transgenic flies, containing Lef/Tcf binding sites comparable to those in TOPFLASH, is not expressed in any embryonic cells, even under conditions of ubiquitous expression of the Wingless ligand ). More significantly, the fact that natural Lef/Tcf-activated enhancers require additional activators for proper expression (Carlsson et al 1993;Giese et al 1995;Brannon et al 1997;McKendry et al 1997;Szuts et al 1998;Nishita et al 2000;Darken and Wilson 2001) indicates that Lef/Tcf binding sites are insufficient for normal target gene activation in their native cis-regulatory contexts.…”
Section: Spres Alone Are Poor Reporters Of Signaling Activity In Vivomentioning
confidence: 99%